PEMBERDAYAAN MASYARAKAT DALAM MENGELOLA KEAMANAN PANGAN ASAL HEWAN - Alifianita Anake Yansri (JPM: Jurnal Pengabdian Masyarakat, 2026)
Animal food safety is a crucial aspect of maintaining public health, yet it still faces various challenges at the community level, such as low knowledge, skills, and awareness regarding hygiene and sanitation. This community service activity aims to increase community capacity in managing animal food safety through an empowerment approach. Implementation methods include outreach, training, hands-on practice, and mentoring for the community and food businesses. Evaluation was conducted through pre- and post-tests to measure knowledge gains, and observations to assess changes in participants' skills and practices. The results of the activity showed an increase in participants' knowledge, attitudes, and skills in applying food safety principles, such as maintaining the cleanliness of ingredients and equipment, and implementing good handling practices. However, there are still obstacles such as limited facilities and old habits that have not fully changed. Overall, this activity is effective in empowering the community and can serve as a model for improving animal food safety, which impacts public health and well-being.